Butterfly pea flower-infused quinoa starch film as a pH indicator for shellfish freshness assessment - Mohammad Rashedi, Ismail Fitry; Shaikh Ahmad, Siti Nur Syahirah; Abdul Salam, Nur Nabilah Hasanah (Malaysian Society of Analytical Sciences, 2024)
The pH indicator film has been utilised in food packaging to guarantee quality and safety as well as to track the freshness of perishable food in real-time. However, previous studies have concentrated on synthetic dyes, so this study investigated the use of butterfly pea flower (BPF) which contains anthocyanin, a natural pigment that is sensitive to a wide pH range. Quinoa starch (QS) contains 10-21% amylose with a small starch granule size of around 1 µm that allows for easier dispersion, making it a promising material to produce pH indicator films. BPF extract was incorporated into QS matrix films as a pH indicator to monitor the freshness of different types of shellfish (blood cockles and short-necked clams) stored at 4°C. The quinoa starch-fish gelatine butterfly pea flower extract (QS/F-BPF) films were developed with different concentrations of BPF (5% and 10%), and then their characteristics including physical appearance, colour, thickness, water vapour permeability (WVP), moisture content, and colour responses were evaluated at different pH values (pH 1-12). The addition of different concentrations of BPF to the quinoa-gelatine based film did not significantly affect the thickness, moisture content, and WVP. Meanwhile, the micrograph of the films showed good surface morphology. The colour and pH of the QS/F-BPF film were examined every two days for six days of storage of shellfish at 4°C, with the colour changing from blue to green with increasing pH on day 6, indicating spoilage. In conclusion, the QS/F-BPF pH indicator film is effective for monitoring the freshness of different types of shellfish stored in chiller conditions.